2011
DOI: 10.1371/journal.pone.0021831
|View full text |Cite
|
Sign up to set email alerts
|

Facultative Symbiont Infections Affect Aphid Reproduction

Abstract: Some bacterial symbionts alter their hosts reproduction through various mechanisms that enhance their transmission in the host population. In addition to its obligatory symbiont Buchnera aphidicola, the pea aphid Acyrthosiphon pisum harbors several facultative symbionts influencing several aspects of host ecology. Aphids reproduce by cyclical parthenogenesis whereby clonal and sexual reproduction alternate within the annual life cycle. Many species, including the pea aphid, also show variation in their reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
164
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(169 citation statements)
references
References 58 publications
4
164
0
1
Order By: Relevance
“…These are known to provide protection to their hosts against heat stress and parasitoid infection, respectively (27), but symbionts may be costly to maintain outside specific ecological conditions (28). Although the reduction in host fitness recorded here indicates a cost of infection to hosts, such costs are likely dependent on both the symbiont and host genotypes (6,7,37,38). However, recent work on Hamiltonella-infected aphids indicates that in the absence of parasitoid wasps, against which Hamiltonella can provide considerable protection, harboring the symbiont may be universally costly, regardless of genetic background, although the extent of these costs varies (7,38).…”
Section: Discussionmentioning
confidence: 82%
“…These are known to provide protection to their hosts against heat stress and parasitoid infection, respectively (27), but symbionts may be costly to maintain outside specific ecological conditions (28). Although the reduction in host fitness recorded here indicates a cost of infection to hosts, such costs are likely dependent on both the symbiont and host genotypes (6,7,37,38). However, recent work on Hamiltonella-infected aphids indicates that in the absence of parasitoid wasps, against which Hamiltonella can provide considerable protection, harboring the symbiont may be universally costly, regardless of genetic background, although the extent of these costs varies (7,38).…”
Section: Discussionmentioning
confidence: 82%
“…The lack of expected benefits identified in this study suggests that North American X-type is not a conditional mutualist like the other common aphid HFS. It is also unlikely that X-type invades pea aphid populations as a reproductive manipulator, as pea aphids primarily reproduce asexually, although some reproductive manipulation has been seen with Spiroplasma-infected pea aphids during their sexual phase (44). Preliminary transmission experiments in the lab found high vertical transmission rates (Ͼ99%) and no instances of horizontal (i.e., infectious) transmission, together indicating that X-type is primarily maternally transmitted, similar to other common pea aphid HFS (45).…”
Section: Discussionmentioning
confidence: 99%
“…For example, removal of a bacterial symbiont from the fungus Rhizopus microsporus completely eliminates vegetative growth by preventing production of sporangia or spores [1]. Among plants, the presence and identity of mycorrhizal fungal symbionts can change relative rates of seed production and vegetative replication of the host [2 -4], and numerous studies have demonstrated the effects of endosymbionts on basic reproductive processes in insects [5][6][7][8][9]. Evidence from symbiotic cnidarians reveals that loss of symbionts can reduce sexual reproduction [10,11], and a change in the symbiont complement can transform mutualistic partners to parasites [12].…”
Section: Introductionmentioning
confidence: 99%